Faktor Penghambat Komunikasi Interpersonal dalam Proses Konseling Individual: Sebuah Systematic Literature Review - Izza Zahiyah Aqly; Indhy Febriyanti Aryunda Sukma; Ifa Nishfatul Laily; Safina Nahda; Darmawati (Universitas Muria Kudus, 2026)
Communication is indeed the heart of human interaction, but in reality, the process of exchanging messages does not always run smoothly. In individual counseling sessions, various obstacles such as mechanical constraints, semantic interference, and even human factors often become unavoidable barriers. This study aims to dig deeper into the factors that actually hinder the effectiveness of interpersonal communication. We also used a literature review method, our primary focus not on numbers or field interview results, but rather on in-depth narrative and descriptive analysis from various existing scientific literature. The results show that communication barriers are dominated by human factors such as gaps in perception and psychological conditions, in addition to mechanical constraints in digital communication media. Through this literature review, it is hoped that new insights will emerge that can help counseling practitioners minimize communication disruptions in the future.